RELIEF EVOLUTION MODEL OF KANIV NEAR-DNIPER AREA ON THE BASE OF DIFFERENCE ANALYSIS OF BASE LEVEL AND VERTEX HYPSOMETRY SURFACES - Tustanovska, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Structural-morphometric analysis and study of Kaniv Near-Dniper relief with the using of the spatial GIS-analysis has been carried out. Difference analysis of base level and vertex hypsometry surfaces allowed to define the character of neotectonic movements, deep erosion and accumulation during the relief formation of this region. The relief morphology evolution character during each neotectonic stage has been described.